Analysis of the uterine artery pulsatility index on the day of endometrial transformation and pregnancy outcomes of patients undergoing frozen–thawed embryo transfer - Li, Li; Du, Mingze; Wu, Sheling; Wen, Caiyuzhu; Kong, Pingping; Zhang, Junwei; Guan, Yichun (Frontiers in Endocrinology, 2024)
Objective: The objective was to analyze the impact of the uterine artery pulsatility index (PI) on pregnancy outcomes by measuring uterine artery blood flow on the day of endometrial transformation in patients undergoing frozen–thawed embryo transfer (FET). Methods: This was a case‒control study. In total, 2,036 patients who underwent FET at the Third Affiliated Hospital of Zhengzhou University from October 2019 to September 2020 were included. The patients were divided into a clinical pregnancy group and a nonclinical pregnancy group according to pregnancy outcome. A multivariate logistic regression model was used to analyze the factors affecting the clinical pregnancy rate. The receiver operating characteristic (ROC) curve was used to determine the optimal mean PI cutoff value of 1.75. After 1:1 propensity score matching (PSM), 562 patients were included. For statistical description and analysis, the patients were divided into two groups: a group with a mean PI > 1.75 and a group with a mean PI ≤ 1.75. Results: The clinical pregnancy group included 1,218 cycles, and the nonclinical pregnancy group included 818 cycles. There were significant differences in female age (P<0.01), infertility type (P=0.04), baseline follicle-stimulating hormone level (P=0.04), anti-Müllerian hormone (AMH) level (P<0.01), antral follicle count (P<0.01), number of transferred embryos (P=0.045) and type of transferred embryo (P<0.01). There was no significant difference in the mean bilateral PI (1.98 ± 0.34 vs. 1.95 ± 0.35, P=0.10). The multivariate analysis results showed that maternal age (AOR=0.95, 95% CI=0.93-0.98, P<0.01), AMH level (AOR=1.00, 95% CI=1.00-1.01, P=0.045), number of transferred embryos (AOR=1.98, 95% CI=1.47-2.70, P<0.01), and type of transferred embryo (AOR=3.10, 95% CI=2.27-4.23, P<0.01) were independent factors influencing the clinical pregnancy rate. The mean PI (AOR=0.85, 95% CI=0.70-1.05; P=0.13) was not an independent factor influencing the clinical pregnancy rate. Participants were divided into two groups according to the mean PI cutoff value of 1.75, and there was no significant difference between the two groups (P > 0.05). Conclusions: In this study, we found that the uterine artery PI on the day of endometrial transformation in patients undergoing FET is not a good predictor of pregnancy outcomes.